Cenozoic tectonic migration in the Bohai Bay Basin, East China. (30th March 2016) - Zhao, Feiyu; Jiang, Suhua; Li, Sanzhong; Zhang, Huixuan; Wang, Gang; Lei, Jianping; Gao, Song
Abstract: Tectonic migration is a common geological process during basin formation and development. However, there are many disputes about the tectonic migration and its dynamic mechanism in the Bohai Bay Basin. By analysis of Cenozoic tectonic, sedimentation and magmatism migration processes in the Bohai Bay Basin, combined with previous studies, the Cenozoic tectonic migration law in the Bohai Bay Basin is summarized in this paper. Affected by the subduction of the Indian Plate to the Eurasian Plate, its far‐field effect of the related eastward asthenospheric extrusion and the subduction of the Pacific Plate to the Eurasian Plate, the Cenozoic Bohai Bay Basin is characterized by the gradual northeastward and eastward/seaward migration of tectonic units. The tectonic migration is accompanied by eastward migrations and younging of faulting, depressions in the Bohai Bay Basin, depocentres and subsidence centres and magmatism. Finally, based on intraplate and plate marginal processes and mechanisms, the tectonic migration mechanism in the Cenozoic Bohai Bay Basin is discussed in this paper. The gradual migration of tectonic–sedimentary‐basin‐forming movements is younger and younger towards the east, resulting from the combined effect of the collision and subduction among the Indian Plate and the Pacific Plate to the Eurasian Plate. Copyright © 2016 John Wiley & Sons, Ltd.